HUBUNGAN MOTIVASI IBU DENGAN KUNJUNGAN POSYANDU BALITA DI POSYANDU DUSUN KUMITIR KECAMATAN JATIREJOÂ Â KABUPATEN MOJOKERTO - Ratnaningsih, Tri; Sari Ning Ati, Ayu (Jurnal Keperawatan Bina Sehat, 2014)
Posyandu was a certain, eact strategy for interventions development viability and expansion. Participation of society aveneeded. The main regulations for society to participating are motivation, people will have a difficulty to participatin in all programs. The purpose of this research was to know there’s connections of mother’s motivation with posyandu do visit rate in Kumitir Posyandu village, Jatirejo subdistrick, Mojokerto regency. This research design were analitic colleational research, with cross sectional phenomenological. Population that used by all mother’s which has childres under 5 years in Kumitir village Jatirejo subdistrict Mojokerto district with non probability sampling technic by taking sampling with total sampling method gained sample of 17 respondet. Research was take on 14 August 2014. Data were taken by using questioner and KMS book/ register book. The result shows that motivation of mother’s are almost half (58,8%), having hard motivation and posyandu visit rate are known in a great measure (70,6%) the routin visit. The gaired data were entered in SPSS version 19.0 count with Crosstab, there’s connections between mother’s motivation with posyandu visit rate in Kumitir Posyandu village staff Jatirejo subdistrict, Mojokerto regency as a medical to increase mother’s motivation to to words posyandu’s visite rate by giving educations and the benefit of posyandu be sides medical staff most increase more cooordination with another in order to optimalizing posyandu activity.Keywords: Motivation, Posyandu Visit Rate, Children Under Five Posyandu